Rules As Theatrical Method In Internet Surveillance Research - Phillips, David J (AoIR Selected Papers of Internet Research, 2016)
This paper will report on a project to take place in May 2016 that will use rule-based theatrical games to explore theories and practices of actuarial surveillance and queer identity.